URGENCY OF ESTABLISHING A COORDINATING BODY FOR THE PILLARS OF THE VILLAGES WITHIN THE VILLAGES LEGAL FRAMEWORK IN INDONESIA - Novitasari, Rikha (Universitas Ekasakti, 2023)
Government affairs in resolving issues of legal needs in the regions must be initiated and started from fundamental changes, especially by gathering and mobilizing citizens so that they can become small organs. This organ has a vital role in providing smoothness in building progress in the villages in administering governance in the villages. The urgency needed to have a rukun desa coordinating body is to provide strengthening of institutional aspects in the Rukun Desa Coordinating Board in the spirit of building self-reliance, mutual cooperation and the welfare of its citizens by providing institutional improvements within the scope of government in the villages. So that harmonization will be formed in villages administration through the Institutions that will be built later with the aim of providing direction for self-management in each Rukun Desa Coordinating Board.